Low serum albumin is an independent risk factor in elderly patients with aggressive B‐cell lymphoma: Results from prospective trials of the German High‐Grade Non‐Hodgkin's Lymphoma Study Group. Issue 1 (13th July 2020) - Hohloch, Karin; Ziepert, Marita; Truemper, Lorenz; Buske, Christian; Held, Gerhard; Poeschel, Viola; Chapuy, Bjoern; Altmann, Bettina
Abstract: Serum albumin a well‐known risk factor predicting outcome in many solid tumors. We explore the role of low serum albumin (≤3.5 g/dL) as an independent risk factor in elderly patients with aggressive B‐cell lymphoma. Outcome of 429 patients treated with R‐CHOP‐14 in the RICOVER‐60 trial and available serum albumin were analyzed in this retrospective study. Of the 429 patients in the RICOVER‐60 trial, 137 (32%) had low and 292 (68%) had normal serum albumin levels (>3.5 g/dL). In the low albumin group, patients had significantly higher International Prognostic Index (IPI), bulky disease, extralymphatic involvement, and B‐symptoms. Event‐free survival (EFS) ( P < .001), progression‐free survival (PFS) ( P < .001), and overall survival (OS) ( P < .001) were significantly inferior for patients with low compared to those with normal serum albumin. Multivariate analysis adjusted for IPI shows following Hazard ratios (HR) for low serum albumin: EFS (HR = 1.5; 95% confidance interval [CI] [1.1; 2.1], P = .009), PFS (HR = 1.7; 95% CI [1.2; 2.4], P = .001) and OS (HR = 1.6; 95% CI [1.1; 2.3], P = .006). Results were confirmed in 185 patients from the DENSE‐R‐CHOP‐14 and SMARTE‐R‐CHOP‐14 trials. In conclusion, low serum albumin is an independent risk factor in elderly patients with aggressive B‐cell lymphoma treated with R‐CHOP.